Genetic association of OPR genes with resistance to Hessian fly in hexaploid wheat - Tan, Chor Tee; Carver, Brett F.; Chen, Ming-Shun; Gu, Yong-Qiang; Yan, Liuling (My University, 2013)
Background: Hessian fly (Mayetiola destructor) is one of the most destructive pests of wheat. The genes encoding 12-oxo-phytodienoic acid reductase (OPR) and lipoxygenase (LOX) play critical roles in insect resistance pathways in higher plants, but little is known about genes controlling resistance to Hessian fly in wheat. Results: In this study, 154 F[subscript 6:8] recombinant inbred lines (RILs) generated from a cross between two cultivars, ‘Jagger’ and ‘2174’ of hexaploid wheat (2n = 6 × =42; AABBDD), were used to map genes associated with resistance to Hessian fly. Two QTLs were identified. The first one was a major QTL on chromosome 1A (QHf.osu-1A), which explained 70% of the total phenotypic variation. The resistant allele at this locus in cultivar 2174 could be orthologous to one or more of the previously mapped resistance genes (H9, H10, H11, H16, and H17) in tetraploid wheat. The second QTL was a minor QTL on chromosome 2A (QHf.osu-2A), which accounted for 18% of the total phenotypic variation. The resistant allele at this locus in 2174 is collinear to an Yr17-containing-fragment translocated from chromosome 2N of Triticum ventricosum (2n = 4 × =28; DDNN) in Jagger. Genetic mapping results showed that two OPR genes, TaOPR1-A and TaOPR2-A, were tightly associated with QHf.osu-1A and QHf.osu-2A, respectively. Another OPR gene and three LOX genes were mapped but not associated with Hessian fly resistance in the segregating population. Conclusions: This study has located two major QTLs/genes in bread wheat that can be directly used in wheat breeding programs and has also provided insights for the genetic association and disassociation of Hessian fly resistance with OPR and LOX genes in wheat.
Citation: Tan, C., Carver, B., Chen, M., Gu, Y., & Yan, L. (2013). Genetic association of OPR genes with resistance to Hessian fly in hexaploid wheat. BMC Genomics, 14(1). https://doi.org/10.1186/1471-2164-14-369
Keywords: Hessian fly resistance; Insect resistance pathway; Lipoxygenase (LOX); 12-oxophytodienoic acid reductase (OPR); Quantitative trait loci (QTL); Wheat